Kader Wisata Berbasis Digital di Desa Cibiru Wetan Kecamatan Cileunyi Kabupaten Bandung Provinsi Jawa Barat - Herlinawati, Erna; Gunawan, Syam; Yulia Wijaya, Dina; Hendra Saputro, Arie; Chandra Jaya, Rama (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Development is needed to manage existing resources well. Empowerment activities aim to help the community achieve social and economic prosperity. One potential empowerment strategy is to build the tourism sector according to potential in the social, economic and cultural fields so that it has implications for increasing the usefulness of resources for all parties involved in it, both government and society. Through tourism at the tourist attractions in Cibiru Wetan Village, the industry will develop more rapidly with the goal to be achieved, namely programs that are beneficial to the community, the community is involved starting from the planning, implementation, management, monitoring and evaluation process, as well as maximizing resource potential. owned, whether human (society), natural (natural potential) or economic (bugdet funds or donations) resources. Apart from that, tourist villages offer new experiences, living at one with rural nature, breathing fresh air, far from pollution and noise, experiencing and being involved in local community activities, in the sense that tourists don't just see the beauty of nature, but can live in it. Tourists can fully experience and enjoy the natural and social culture of the village. The stages of the service method are (1) Problem analysis, (2) Focus Group Discussion (FGD) with partners to determine the priority scale, (3) Training and Mentoring, (4) Development of Infrastructure, (5) Monitoring and Evaluation and Program Sustainability. The target output of this activity is, in addition to increasing the skills of partners, also publication in the SINTA 3 National Journal, West Java Tribune Mass Media and publication of video content of the implementation of the activity as well as additional output in the form of IPR. The service technology readiness level is at level 2 leading to level 3. The results of the activities are: increasing the knowledge and skills of partners through training and mentoring, fulfilling the development of infrastructure, and establishing university and village partnerships.